The commentary of St. Thomas on the De Caelo of Aristotle - Weisheipl, James A. (Sapientia, 1974)
The "commentary" or Sententia de caelo et mundo of St. Thomas is a work of great maturity and profundity. It is one of Thomas's last writings, and it reveals a breadth of scholarship and achievement wanting, for the most part, in his earlier Aristotelian comentaries, such as those on the Ethics, Physics, De anima, and early parts of . the Metaphysics; but it comes to grips with profound problems of Aristotelianhpi loso bpy inherent in the conflictingg views of Greek and Arab commentators. I. T. Eschmann rightly noted that "itrepresents; the high water-mark of St. Thomas's expository skill".' In long subtle digressions, Thomas discusses and evaluates the views of other commentators reported by Simplicius, as well as the views of Simplicius himself, who is a primary source in this commentary. As in earlier commentaries, Thomas was also concerned with the teaching of Averróes, which deeply influenced the masters in arts at Paris in the late 1260s and throughout the 1270s. The excessive adoption of Averroes by masters in arts resulted in the condemnation of 13 Averroes theses on Dec. 10, 1270, by the bishop of Paris, Etienne Tempier, and in the- more sweeping condemnation by the same bishop on March 7, 1277. Simplicius and Averroes are in fact the two basic sources for Thomas's commentary on De caelo...